Die Henne oder das Ei? azzo oder -zo? Weitere Spekulationen zu einem pronominalen Problem des Harari - Wagner, Ewald (Aethiopica, 2024)
There is no consensus among Ethiopists on the question of whether the Harari enclitic possessive suffix 3sg. m. -zo is an eroded form of the personal pronoun azzo (Appleyard, Huehnergard and Pat-El) or whether azzo emerged from -zo by being prefixed with another morpheme (Cerulli, Leslau). The present article attempts a solution to this problem by considering it against the background of the overall development of the pronominal system of Harari (personal, possessive and demonstrative pronouns), on the one hand, and the historical areal context, on the other. The author considers -zo as the more likely starting point and proposes a fivestage development for the emergence of azzo. In the final section, however, the reverse process, the development of -zo from azzo, is briefly discussed as a possible alternative.